Achieving food security and industrial development in Malawi: Are export restrictions the solution? - Aragie, Emerta A.; Pauw, Karl; Pernechele, Valentina (International Food Policy Research Institute, 2016)
Restrictions on exports of staples or cash crops are frequently imposed in developing countries to promote food security or industrial development goals. By diverting production to the local market, these policies aim to reduce prices and increase the supply of food or intermediate inputs to the benefit of consumers or downstream industrial users. Although export restrictions reduce aggregate welfare, they are attractive to policymakers: Governments gain support when they are seen to keep consumer prices low; likewise, politicians are swayed by industrial lobbyists who promise increased value-addition in exchange for access to cheaper inputs. This study weighs in on the debate around the desirability of export restrictions by simulating the economy-wide effects of Malawi’s longstanding maize export ban as well as a pro-posed oilseed export levy intended to raise value-addition in processing sectors. Our results show that, while export restrictions may have the desired outcome in the short run, producers respond to weakening market prospects in the longer run by restricting supply, often to the extent that the policies become self-defeating. Specifically, maize export bans only benefit the urban non-poor, while poor farm households experience income losses and reduced maize consumption in the long run. The oilseed export levy is equally ineffective: Even when export tax revenues are used to subsidize processors, gains in industrial value-addition are outweighed by declining agricultural value-addition as production in the fledgling oilseed sector is effectively decimated. The policy is further associated with welfare losses among rural households, while urban non-poor households benefit marginally.